‘that's a scientific fact’: Christine Brooke-Rose's Experimental Turn - Guy, A (Modern Humanities Research Association, 2016)
The critical reception of the British novelist Christine Brooke-Rose has been governed largely by Brooke-Rose's own endorsement, in her parallel career as a literary critic, of structuralism and poststructuralism. Brooke-Rose's experimental turn as a novelist, however, pre-dates this development in her critical world-view. This article draws attention to the intellectual context of Brooke-Rose's experimental turn, considering the ways in which, in fiction and in criticism, she drew on the Uncertainty Principle of the physicist Werner Heisenberg, seeking to link it to the literary innovations of the French nouveau roman in order to ground her interrogations of narrative.